2008
DOI: 10.1111/j.1467-9663.2008.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Distant Friends Online? Rural and Urban Adolescents’ Communication on the Internet

Abstract: This study explores how rural and urban adolescents use the Internet as a tool for communication in their social environment. It aims to analyse the differences in the use of the Internet to overcome environmental constraints between urban and rural adolescents. In this paper, environmental constraints are defined in two ways: (1) The lack of contacts that a person may have in his/her local environment and (2) The distance between the contacts that prevents him/her from having face‐to‐face social interaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The Internet's provision of tools toward the creation of increasingly effective social networks (Dooris, Sotireli, and Van Hoof 2008;Ellison, Steinfield, and Lampe 2007;Hargittai 2008) along with an enhanced capability toward the exploration and development of identity (McMillan and Morrisson 2006;Moinian 2006) help to explain its ever increasing popularity among young people today. The social mechanisms at work in this Internet arena can be categorized under the rubric of social media.…”
Section: Youth Online Use Anonymity and Sdtmentioning
confidence: 99%
“…The Internet's provision of tools toward the creation of increasingly effective social networks (Dooris, Sotireli, and Van Hoof 2008;Ellison, Steinfield, and Lampe 2007;Hargittai 2008) along with an enhanced capability toward the exploration and development of identity (McMillan and Morrisson 2006;Moinian 2006) help to explain its ever increasing popularity among young people today. The social mechanisms at work in this Internet arena can be categorized under the rubric of social media.…”
Section: Youth Online Use Anonymity and Sdtmentioning
confidence: 99%
“…In the micro-level literature, the research is aimed at finding out how people's lives and social positions are affected by the growing importance of ICTs, using social networks and social capital as conceptual bases (see for example Boase, 2010;Stern and Adams, 2010;Stern et al, 2011). Most micro-level literature, however, focuses on specific groups of mostly vulnerable people (see also Warren, 2007), such as rural children (Valentine and Holloway, 2001), rural youth (Laegran, 2002;Dooris et al, 2008;Awan and Gauntlett, 2012), rural women (Rubinoff, 2005), older people (Park, 2008), rural patients (Miller and West, 2009), or people living in remote areas, such as employees and teleworkers in rural areas (Simpson et al, 2003;Laegran, 2008;Brownlee et al, 2010), as well as farmers (Briggeman and Whitacre, 2010;Jeffcoat et al, 2012) and entrepreneurs (Grimes, 2000(Grimes, , 2003. A majority of these studies (11 of 13 papers) show that rapid digital developments make these groups more vulnerable to digital and social exclusion.…”
Section: Digital Inequalities Research (31 Papers)mentioning
confidence: 99%
“…They also found that young people from non-urban areas played online games more frequently for want of alternative entertainment opportunities. Dooris et al (2008) noted that young people from urban areas obtained more emotional support through the internet than their 'rural' peers. This finding was based on a survey with 124 pupils attending university preparatory education in the Netherlands.…”
Section: Research On Young People's Internet Usementioning
confidence: 99%
“…Besides these risks, the internet also holds a lot of opportunities for enlarging or maintaining social networks (Dooris et al, 2008;Ellison et al, 2007;Hargittai, 2008), for further identity development (McMillan and Morrisson, 2006;Moinian, 2006) and for social support (Dooris et al, 2008;Hlebec et al, 2006). In the same way, it offers opportunities for education too.…”
Section: Learning Is More Than Information Isn't It?mentioning
confidence: 99%